No Treatment Benefits of Local Administration of Insulin-like Growth Factor-1 in Addition to Heavy Slow Resistance Training in Tendinopathic Human Patellar Tendons: A Randomized, Double-Blind, Placebo-Controlled Trial With 1-Year Follow-up. Issue 9 (July 2021) - Olesen, Jens L.; Hansen, Mette; Turtumoygard, Ida F.; Hoffner, Rikke; Schjerling, Peter; Christensen, Jan; Mendias, Christopher L.; Magnusson, Peter S.; Kjaer, Michael
Background: Heavy slow resistance (HSR) training is currently recommended as part of the treatment of patellar tendon tendinopathy. However, treatment success is not reached in all patients, and combinations of different treatments could be beneficial. Local administration of insulin-like growth factor-1 (IGF-1) in humans has been shown to quickly stimulate tendon collagen synthesis. Purpose: To study whether IGF-1 injections combined with HSR training enhance tendon synthesis, tissue structure, and patient satisfaction versus saline injection combined with HSR training in patients with patellar tendinopathy. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Forty patients (age 18-50 years) with unilateral patellar tendinopathy undertook HSR training (3 times a week for 12 weeks) and received intratendinous IGF-1 injections (1 mg IGF-1 per dose) or isotonic saline injections (sham injections) at baseline and after 1 and 2 weeks of training. The primary outcome was collagen synthesis parameters after 12 weeks (primary endpoint). The secondary outcomes were patient-reported outcomes (scores on the Victorian Institute of Sport Assessment–Patella [VISA-P] and visual analog scale [VAS] for pain) and structural changes before the initiation of treatment and at week 3, week 12, and 1 year after the initiation of treatment. Results: Analysis of the patellar tendon biopsy specimens at 12 weeks showed that collagen mRNA and total RNA were increased in the tendinopathic tendons compared with the contralateral healthy tendons regardless of treatment with IGF-1 or saline. Similarly, no difference between the groups was seen in tendon thickness and Doppler activity at week 12 or at 1-year follow-up. The combination of HSR training and IGF-1 injections significantly improved VISA-P and VAS pain scores after 3 weeks, whereas the overall responses after 12 weeks and at 1-year follow-up were identical in the 2 groups. Conclusion: Although a small, immediate clinical response to IGF-1 injections was seen when combined with training, no additional long-term effect of intratendinous IGF-1 was observed on structural and clinical outcomes in patients with patellar tendinopathy. Registration: NCT01834989 (ClinicalTrials.gov identifier)